Polymorphic Mutation Frequencies of Clinical and Environmental Stenotrophomonas maltophilia Populations - Turrientes, María Carmen (American Society for Microbiology (ASM), 2010)
Mutation frequencies were studied in 174 Stenotrophomonas maltophilia isolates from clinical and nonclinical environments by detecting spontaneous rifampin-resistant mutants in otherwise-susceptible populations. The distribution of mutation frequencies followed a pattern similar to that found for other bacterial species, with a modal value of 1 × 10(−8). Nevertheless, the proportion of isolates showing mutation frequencies below the modal value (hypomutators) was significantly higher for S. maltophilia than those so far reported in other organisms. Low mutation frequencies were particularly frequent among environmental S. maltophilia strains (58.3%), whereas strong mutators were found only among isolates with a clinical origin. These results indicate that clinical environments might select bacterial populations with high mutation frequencies, likely by second-order selection processes. In several of the strong-mutator isolates, functional-complementation assays with a wild-type allele of the mutS gene demonstrated that the mutator phenotype was due to the impairment of MutS activity. In silico analysis of the amino acid changes present in the MutS proteins of these hypermutator strains in comparison with the normomutator isolates suggests that the cause of the defect in MutS might be a H683P amino acid change.